The Bible, Power and Wealth in in Africa: A Critique of the Prosperity Gospel in Sub-Saharan Africa - Wafawanaka, Robert (Navigating African Biblical Hermeneutics: Trends and Themes from our Pots and our Calabashes, 2018)
[book abstract] This collection interrogates and engages the biblical text, colonial and postcolonial subjectivities and cultural assumptions, as well as lived experiences that encompass varying Africana contexts and Diasporas. In order to do this, it deploys methodologies, exegetical analyses and critical and constructive communal epistemologies. Framed by historical, literary, cultural and theological engagements of issues around wealth and power, gender, sexualities and masculinities, HIV and AIDS, as well as the crises of war and mass violence, the book will be very useful for students, academics, clergy and laity committed to Africana-conscious epistemologies and methodologies, and the impact on biblical studies.